A modified side-sensitive synthetic chart to monitor the process mean. Issue 3 (4th May 2018) - Shongwe, Sandile C.; Graham, Marien A.
Abstract: In this paper, we propose a modified side-sensitive (MSS) synthetic chart which signals only if all the consecutive plotting statistics that lead to an out-of-control event fall on one side of the centre line, unlike the non-side-sensitive, standard and revised side-sensitive synthetic charts that also signal even when some of the plotting statistics fall on opposite sides of the centre line. Moreover, we use the Markov chain imbedding technique to study and compare the zero-state and steady-state average run-length (ARL), extra quadratic loss, average ratio of the ARLs and performance comparison index of the proposed MSS chart with other Shewhart-type synthetic and runs-rules charts. The synthetic chart with this MSS feature has a better overall zero-state and steady-state performance than the existing synthetic charts and hence makes it a strong contender in many applications where existing synthetic charts are currently used.